"Filhos da África na UFRR": vivências e experiências dos estudantes PEC-G - Lourenço, Izaulina Videira Ramos (2016)
This work aims to analyze the life experiences of 28 students migrants from various African countries, aged 18-23 years, in the period of 2012-2015. These African students are linked to the Covenant of Graduate Student Program - PEC-G at the Federal University of Roraima and is, nowadays, the majority of foreign students who have entered in undergraduate courses of the institution, whom actually started coming to Boa Vista since 2012, year that begun the elaboration of a field diary about their daily life. As this work is a participatory research as an ethnographic procedure, the impressions written in the diary and the result of the interviews with nine deponents were analyzed and exposed throughout the chapters of this dissertation, being interpreted what was said or omitted in the narratives of the students, verifying common expressions among them, jargon, descriptions of experienced events that left their mark in their lives, including cases of discrimination, racism in border area, stereotype and other elements which have been aggregated in the analysis of the social phenomena. It concludes that despite the existence of strikes, sickness, lack of financial resources due to family problems and others contretemps faced by PEC-G students, learning has been intense, diversified, leading to individual and collective reflection on life projects, providing discussions of black conscience, racism, valuing of African culture, seeking recognition and respect stand at a critical backdrop of racial prejudice in Brazil and worldwide.